Nonlinear reflection ellipsmetry for an anisotropic uniaxial crystal then optical axis lies in the plane of incidence - N.A. Matveeva; R.V. Schelokov; V.V. Yatsishen (Физика волновых процессов и радиотехнические системы, 2013)
A new method of ellipsometry was considered Nonlinear ellipsometry, allowing to determine nonlinear characteristic of a medium. Angular spectra of nonlinear reflection ellipsometry for uniaxial crystals such as Beta-Barium Borate, Lithium Niobate, Proustite were calculated and plotted at different orientations of the optical axis. Also the high sensitivity of method in the diagnosis of the crystal parameters was showed.